Effects of the anomalous magnetic moments of the quarks on the neutral pion properties within a SU(2) Nambu–Jona Lasinio model - Aguirre, Ricardo Miguel (2021)
The properties of the neutral pion in quark matter under the influence of an external magnetic field are studied. The effects of the anomalous magnetic moments (AMM) of the quarks at finite density is considered. The inclusion of the AMM into the NJL model gives rise to additional magnetic effects. In particular the Dirac sea produce new divergences in the vacuum contributions, which depend explicitly on the magnetic field. An improper treatment of these contributions is the source of unphysical results, as emphasized in recent investigations. The pion polarization function is evaluated in the random phase approximation using analytic regularization and a subtraction scheme to deal with such divergencies. This procedure is combined with the standard three momentum cutoff, and reduces to it for vanishing magnetic intensity. The pion mass and coupling constant are evaluated for a wide range of magnetic intensity and baryonic density.